(untitled) (Research, Society and Development, 2022)
The present work aims to reactivate an "agricultural Mandala", making it a pedagogical tool to help in professional and technological education, together with students of the Technical course in the Environment of the Cabedelo campus, of the Federal Institute of Paraiba, who followed the entire process. Through practical classes. During its reactivation process, agroecological-based techniques were implemented together with the students, who were later able to attest to their validity in consolidating their knowledge through sustainable actions practiced in the aforementioned “Mandala”. Techniques such as: the composting process, the importance of organic fertilization, elimination of outputs in the system, use of woodworking residues, from the coffee industry, use of vegetable fibers (coconut) as mulch to protect the soil and retain moisture were demonstrated. , use of PET bottles (in the construction of the mandala), polyculture practice, among others. Different vegetables were preferably planted such as: lettuce, coriander, peppers, garlic, among others, in addition to maintaining aromatic and medicinal species that already existed there, such as: lemongrass, mint, lemon balm, etc. Weekly the plants were cultivated, watered, weeded, etc. Finally, the evaluation of the experience and the tool was carried out, tabulating the results of the data through simple statistics, which resulted in the approval by the vast majority of teachers of the use of this tool, including providing them with the ability to replicate the experience and establish of the concepts used in it.